Ethnographic Seeping in Mid-Twentieth-Century Mexican Cinema - García Blizzard, Mónica (Revista Canadiense de Estudios Hispánicos, 2022)
This article argues that the impact of what Lomnitz has termed Mexico’s “national anthropology,” which structured indigenismo and mestizaje as official institutional projects, also reverberated in the representation of Indigeneity in Mexican mid-twentieth-century cinema. Proposing the concept of “ethnographic seeping,” this study illustrates how the ethnographic mode recurs parenthetically in commercial and independent Indigenous-themed narrative films intended for popular audiences and/or prestige venues. While ethnographic seeping enacted a distanced and appropriative relationality between spectators and Indigenous Mexicans, it also functioned critically to contest official aims and perspectives.